Structural insight into ASH1L PHD finger recognizing methylated histone H3K4 and promoting cell growth in prostate cancer - Yu, Miaomiao; Jia, Yanjie; Ma, Zhanchuan; Ji, Donglei; Wang, Chunyu; Liang, Yingying; Zhang, Qiang; Yi, Huanfa; Zeng, Lei (Frontiers in Oncology, 2022)
ASH1L is a member of the Trithorax-group protein and acts as a histone methyltransferase for gene transcription activation. It is known that ASH1L modulates H3K4me3 and H3K36me2/3 at its gene targets, but its specific mechanism of histone recognition is insufficiently understood. In this study, we found that the ASH1L-PHD finger interacts with mono-, di- and tri-methylated states of H3K4 peptides with comparable affinities, indicating that ASH1L-PHD non-selectively binds to all three methylation states of H3K4. We solved NMR structures picturing the ASH1L PHD finger binding to di-methylated H3K4 peptide, and found that a narrow binding groove and residue composition in the methylated-lysine binding pocket restricts the necessary interaction with the dimethyl-ammonium moiety of K4. In addition, we found that ASH1L protein is overexpressed in castrate-resistant prostate cancer (CRPC) PC3 and DU145 cells in comparison to prostate cancer LNCaP cells. Knockdown of ASH1L modulated gene expression and cellular pathways involved in apoptosis and cell-cycle regulation, and consequently induced cell-cycle arrest, cell apoptosis and reduced colony forming abilities in PC3 and DU145 cells. Overexpression of the C-terminal core of ASH1L but not the PHD deletion mutant increased the overall H3K36me2 level but had no effect on the H3K4me2/3 level. Overall, our study identifies ASH1L PHD finger as the first native reader that non-selectively recognizes three methylation states of H3K4. Additionally, ASH1L is required for deregulation of cell cycle and survival in prostate cancers.